Comparative Effects of Different Dosages of hCG on Follicular Development in Postpartum Dairy Cows With Cystic Ovarian Follicles - Ono, Tetsushi; Takagi, Mitsuhiro; Kawashima, Chiho; Wijayagunawardane, Missaka P. B.; Vos, Peter L. A. M.; Taniguchi, Masayasu; Tanihara, Fuminori; Otoi, Takeshige (Frontiers in Veterinary Science, 2018)
The objective of this study was to determine the effects of different intramuscular dosages of human chorionic gonadotropin (hCG) on ovarian follicular development of dairy cows diagnosed with refractory cystic ovarian follicles (COFs). Cows diagnosed with COFs (≧ 25 mm in diameter) were allocated to four treatment groups: hCG-1 (n=3), a single dose of 4,500 IU on day 1; hCG-2 (n=3), 2,250 IU on days 1 and 3; hCG-3 (n=3), 1,500 IU on days 1, 3, and 5; and hCG-C (n=3) received saline on day 1. Blood sampling and ovarian ultrasonographic (US) examinations were performed on days 1, 3, 5, 7, and 14. A progesterone (P4) value < 1 ng/ml was used as an indicator of absence of a functional CL. A significant increase (P < 0.05) in the number of follicles < 4 mm in diameter was observed in the hCG-2 group on day 5. Additionally, there was a significant difference in the number of follicles < 4mm (P < 0.05) between both the hCG-2 and hCG-3 groups compared to the hCG-C group on day 5, and a tendency (P = 0.08) towards a difference in the number of 5-9 mm follicles in groups hCG-3, hCG-2, and hCG-1, compared with the hCG-C group on day 7. The proportion of cows on days 7 and 14 with P4 > 1 ng/ml was 100% (3/3) and 100% (3/3) in group hCG-1; 100% (3/3) and 67% (2/3) in group hCG-2; 67% (2/3) and 100% (3/3) in group hCG-3; and 33% (1/3) and 33% (1/3) in group hCG-C, respectively. Strong tendencies of P4 increases in group hCG-1 (P=0.054) and hCG-2 (P=0.051) were measured after hCG administration. Additionally, P4 values tended to be higher (P=0.07) for group hCG-1 compared to group hCG-C on day 5. The preliminary findings of this study suggest that multiple smaller doses of hCG might be equally effective as a single large dose of hCG in modulating ovarian follicular development in dairy cows with COFs.